Biografi Shaikh Ahmad B. Idris dan Sumbangannya Terhadap Alam Kesufian - Saari, Che Zarrina (Afkar: Jurnal Akidah dan Pemikiran Islam, 2000)
This article is an analytical study of the founder of Ahmadiyyah Order that had spread all over the world including the Malay Peninsula. It tries to gather an information about Shaikh Ahmad b. Idris who played an important role in organizing and developing the order. His thought about religious reformation which has a similarity with Muhammad b. ’Abd al-Wahab has also been discussed to evaluate either the former was influenced by the latter or not. The article also attempts to highlight Shaikh Ahmad b. Idris’s contributions to the sufis’ world.